Venous Thromboembolism Prophylaxis and Risk for Acutely Medically Ill Patients Stratified by Different Ages and Renal Disease Status. (28th January 2019) - Amin, Alpesh; Neuman, W. Richey; Lingohr-Smith, Melissa; Menges, Brandy; Lin, Jay
The objectives of this study were to examine venous thromboembolism (VTE) prophylaxis patterns and risk for VTE events during hospitalization and in the outpatient continuum of care among patients hospitalized for acute illnesses in the United States with stratification by different age groups and renal disease status. Acutely ill hospitalized patients were identified from the MarketScan databases (January 1, 2012-June 30, 2015) and grouped by age (<65, 65-74, ≥75 years old) and whether or not they had a baseline diagnosis of renal disease, separately. Of acutely ill hospitalized patients, 60.1% (n = 10 748) were <65 years old, 15.7% (n = 2803) were 65 to 74 years old, and 24.3% (n = 4344) were ≥75 years old; 32.9% (n = 5892) had baseline renal disease. Among the study cohorts, the majority of patients received no VTE prophylaxis regardless of age or baseline renal status (52.1%-63.6%). Rates of VTE during hospitalization and in the 6 months postdischarge were 4.7%, 4.6%, and 4.5% for patients <65, 65 to 74, and ≥75 years old, respectively, and 6.3% and 3.8% for patients with and without baseline renal disease. The risk for VTE was elevated for 30 to 40 days after index admission regardless of age and renal disease status.